2021
DOI: 10.1021/acsabm.0c01675
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrogen Peroxide-Mediated Cross-Linking and Degradation on Cell-Adhesive Gelatin Hydrogels

Abstract: Hydrogen peroxide (H 2 O 2 ) is widely used for the gelation of aqueous solutions of gelatin derivatives with phenolic hydroxyl groups (Gelatin-Ph) catalyzed by horseradish peroxidase (HRP). Apart from this, H 2 O 2 is known to cause degradation/depolymerization of various polymers. Here, we prepared Gelatin-Ph hydrogels from solutions containing Gelatin-Ph and HRP by continuously supplying H 2 O 2 from the gas phase and investigated the mechanical properties of resultant hydrogels and the behaviors of rat fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
5
13
0
Order By: Relevance
“…Cell morphology analysis showed that while NMuMG/Fucci2 cells also had small and round morphology on the hydrogel obtained through 15 min of exposure to H 2 O 2 , cells cultured on the hydrogel obtained through 120 min of the exposure had an elongated shape, despite having almost similar stiffness (0.40 kPa) with hydrogel obtained through 15 min of the exposure (0.20 kPa) ( Figure 6 b–f). This phenomenon is similar to our previous report in human adipose-derived stem cells (hASCs) and rat fibroblast (3Y1) cells cultured on Gelatin–Ph hydrogel that showed elongated morphology on the hydrogel obtained through 60 min of exposure to H 2 O 2 despite having similar stiffness with hydrogel obtained through 15 min of the exposure [ 31 ]. This phenomenon could be attributed to other factors such as mesoscale topographical changes and mesh size [ 67 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Cell morphology analysis showed that while NMuMG/Fucci2 cells also had small and round morphology on the hydrogel obtained through 15 min of exposure to H 2 O 2 , cells cultured on the hydrogel obtained through 120 min of the exposure had an elongated shape, despite having almost similar stiffness (0.40 kPa) with hydrogel obtained through 15 min of the exposure (0.20 kPa) ( Figure 6 b–f). This phenomenon is similar to our previous report in human adipose-derived stem cells (hASCs) and rat fibroblast (3Y1) cells cultured on Gelatin–Ph hydrogel that showed elongated morphology on the hydrogel obtained through 60 min of exposure to H 2 O 2 despite having similar stiffness with hydrogel obtained through 15 min of the exposure [ 31 ]. This phenomenon could be attributed to other factors such as mesoscale topographical changes and mesh size [ 67 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the applications of using H 2 O 2 for inducing HRP-mediated hydrogelation, no attention has been paid to the contradictory functions of H 2 O 2 for inducing the degradation of the polymers. Recently, we reported that the contradictory function of H 2 O 2 affects the mechanical property of hydrogels, which leads to changes in adhesion of the human adipose-derived stem cells (hASCs) and rat fibroblast cells [ 31 ]. However, the contradictory effect of H 2 O 2 on other cell behaviors, such as cell-cycle progression, has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…At 5.0% w / v , the Gelatin-Ph solution quickly forms hydrogel at room temperature, while at 1.0% w / v , the resultant hydrogels are too weak to handle for experiments. In addition, 1 U mL −1 HRP is used, since previous studies have reported an H 2 O 2 -mediated dynamic of the stiffening and softening of the hydrogels using a similar setup [ 15 , 17 ]. The scanning electron microscope (SEM) observation on the cross-section of the hydrogels showed a porous structure with a pore diameter of 28–42 µm ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have reported that hydrogen peroxide (H 2 O 2 ) could be used to control the physicochemical property of gelatin derivatives possessing phenolic hydroxyl moieties (Gelatin-Ph) hydrogel obtained from horseradish peroxidase (HRP)-catalysed cross-linking [ 15 ]. This system exploits the contradictory effect of H 2 O 2 that simultaneously induces the HRP-catalysed cross-linking as an electron donor while degrading the polymer as an oxidant ( Figure 1 a) [ 15 ]. The advantage of this system is that the mechanical property and molecular weight of the hydrogel can be controlled by a simple adjustment of the air containing H 2 O 2 exposure time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation